Terpenoid Compounds of Lime (Citrus Aurantifolia) Peel by Using Gas Chromatography Mass Spectrometry (GCMS) Method (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2022)
Terpenoid compounds known as essential oils can be used as flavour enhancers and medicinal sources. The Citrus genus is a citrus aurantifolia species. Citrus aurantifolia (Rutaceae) is a fruit type most often consumed by the public. This study aimed to determine the terpenoid compounds contained in lime peel extract (C. aurantifolia). This study used the extraction method for 3 x 24 hours and then continued by using a sonicator. The viscous extract was then analyzed by using a GCMS method. This study obtained that the β-pinene compound for the retention time was 7.92, and the per cent area was 34.81 %. While for the D-limonene compound for the retention time was 6.62, and the per cent area was 20.15 %